Mineralocorticoid Receptors in the Pathophysiology of Vascular Inflammation and Atherosclerosis - Moss, Mary E.; Jaffe, Iris Z. (Frontiers in Endocrinology, 2015)
Atherosclerosis is a chronic inflammatory disease of the vasculature that causes significant morbidity and mortality from myocardial infarction, stroke, and peripheral vascular disease. Landmark clinical trials revealed that mineralocorticoid receptor (MR) antagonists improve outcomes in cardiovascular patients. Conversely, enhanced MR activation by the hormone aldosterone is associated with increased risk of MI, stroke, and cardiovascular death. This review summarizes recent advances in our understanding of the role of aldosterone and the MR in the pathogenesis of vascular inflammation and atherosclerosis as it proceeds from risk factor-induced endothelial dysfunction and inflammation to plaque formation, progression, and ultimately rupture with thrombosis, the cause of acute ischemia. The role of the MR in converting cardiac risk factors into endothelial dysfunction, in enhancing leukocyte adhesion and infiltration into the vasculature, in promoting systemic inflammation and vascular oxidative stress, and in plaque destabilization and thrombosis are discussed. A greater understanding of the mechanisms by which the MR promotes atherosclerosis has substantial potential to identify novel treatment targets to improve cardiovascular health and decrease mortality.